An Integrated Artificial Intelligence (AI) Model in Sharia Banking Contracts: A Solution to Enhance Public Literacy and Understanding - Mahfuzh, Muhammad Ady; Fathurohman, Oman (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
This study aims to develop an integrated Artificial intelligence (AI) model to enhance literacy and public understanding of Sharia bank product contracts in Indonesia. Adopting a qualitative methodology with secondary data, the study explores AI models as tools to improve societal comprehension and decision-making processes. The findings outline a comprehensive AI integration framework that can be implemented across various sectors, including the Fatwa Council, government, Sharia banks, MSMEs, and the general public. The proposed framework comprises eight key stages: the formulation of fatwas and regulations for Sharia contracts, the adjustment of contracts based on data and real-world application, recommendations for refining the execution of Sharia contracts, the implementation of these contracts in financial products, dissemination of relevant contract information, identification of challenges in contract implementation, public education and simulation of Sharia contracts, and addressing public misunderstandings. It is crucial that all stakeholders, including governments, MSMEs, and the public, actively participate in this process, ensuring governmental facilitation and increased public awareness of the positive impact of AI utilization in this context.